Penanaman Nilai-Nilai Patriotisme Dan Nasionalisme Pada Siswa Melalui Pembelajaran PPKn Di SMK Negeri 2 Salatiga - manggaprouw, yesaya sampari; Mediatati, Nani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This study aims to describe the inculcation of the values of patriotism and nationalism in students through PPKN learning in class XI TAV-A SMA Negeri 2 Salatiga. The type of research: descriptive qualitative, research subjects were PPKn teachers and students of class XI TAV-A. Collecting data using observation techniques, interview tests, questionnaires, documentation. Data analysis used descriptive qualitative analysis. The results showed that the inculcation of the values of patriotism and nationalism through Civics learning had been carried out starting from the planning, implementation and evaluation stages. The values of patriotism and nationalism that were instilled were: respecting differences, maintaining unity, being willing to sacrifice, caring about helping friends who are in trouble, being responsible, honest, disciplined and religious. Based on student questionnaire data processing, the effectiveness of Civics learning in instilling the values of patriotism and nationalism is manifested in eight attitudes of students who fall into the very high category with an average value of >3.0